Praktik Otoritas MUI Dalam Menjaga Kerukunan Umat Beragama Di Indonesia : Practice of the MUI Authority in Maintaining Religious Harmony in Indonesia - Tri Bambang Prasetyo; Wahyuddin Bakri (SOSIOLOGIA : Jurnal Agama dan Masyarakat, 2023)
The scope of major issues regarding the harmony of religious life, namely the implementation of laws and regulations, especially Law No. 32 of 2004 concerning government difficulties in its implementation, the development of the religious sector including the five government affairs which are still in the hands of the government, this research tries to find out the practice of authority carried out by religious institutions, especially Islamic teachings as the majority religion in Indonesia, are seen as a sociological phenomenon. This research uses the method of a literature study, collecting library data and references starting from the internet, reading, taking notes, processing research. The collected data are scientific publications filtered by references to books, journal articles. identifying the results of the research referring to the problem "The Practice of MUI Authorities in Maintaining Religious Harmony in Indonesia", the writer observes studying phenomena that occur in society and then analyzes the phenomena from previous research. Issues of authority, especially religious authority, often become an arena of contestation by various groups. religious. By holding on to authority, it is not uncommon for authoritarian actions to be exhibited by judging other groups who are considered to have deviated from the established understanding of religion. It's not just a matter of judgment of "heretical sects", automatically it is also often used to control adherents of other religions. The existence of various fatwa institutions is actually proof of the pluralism of understanding and interpretation of Islam in Indonesia. Among the fatwa institutions, their opinions cannot be mutually denied or eliminated. The diversity of opinions of fatwa institutions is nothing more than a diversity of legal opinions that give space to the public to choose.